Fostering Connections, Nurturing Prospects: A Proposed Communities of Practice Plan in Re-engaging Out-of-School Youth - Diez, Liza; Oris, Rowena; Javier, Jocelyn; Samson, Jomari; Salvador, Marisol; Fabro, Arrianne Michelle (Journal of Interdisciplinary Perspectives, 2024)
This study investigates the effectiveness of Communities of Practice (CoPs) as a strategy to re-engage out-of-school youth (OSY) in the Philippines. The research, utilizing a qualitative multiple case study approach with three OSY participants from Nagtenga, Sta Cruz, Ilocos Sur, explores themes of belonging, social connections, and prospects. Findings highlight the challenges faced by OSY, including isolation, limited social networks, and uncertain futures. Barriers to CoP participation include accessibility, financial constraints, and balancing commitments. A proposed CoP plan aims to create a supportive environment for OSY to develop skills, build connections, and drive positive change within their communities. This study emphasizes the need for tailored community-driven initiatives to address the unique needs of OSY and promote their successful re-engagement in education and society. Further research is recommended to evaluate the long-term impact of CoPs and develop scalable implementation strategies.